The Concept of Qalbu Education According to Imam Ghazali - Ulum, M. Alfanny Fahmil; Fahmi, Muhammad (Maharot : Journal of Islamic Education, 2023)
This article is intended to explain the concept of qalb education according to Imam Ghazali. Qualitative methods based on library research are used for the above purposes by placing text as a research source. The data obtained was then processed using qualitative methods, then interpreted using descriptive analytical methods. The following is the formulation of the results: the peak of human perfection is the balanced role of the mind and heart in developing the human spirit. So the core target of education is the perfection of human morals by cultivating his spirit. So education is said to be successful in targeting targets if it is able to produce people who have akhlaq al-karimah. The second reason and qalb are inner potentials that play a role in the humanistic realm, both in the form of cognition, perception, and others in an effort to form a good moral order.